The RBV in relation to Turnarounds: The Case Study Of Jarvis Plc - Inngern, Roselyn (2010)
The study examines the inability of a turnaround firm to sustain enhanced performance, whereby they detrimentally faced decline post turnaround. The study sought to uncover the reasons for such decline by conducting an in depth analysis of the company over a 20 years period, drawing on the Resource Based View to enhance analysis. Annual reports for the whole period alongside various newspaper articles aided the depiction and understanding of reasons for decline. The resources of the firms significantly affected its performance, whereby unrelated diversification by the firm led to adverse consequences in profits and performance. This highlights the relative importance of managers in acknowledging the resource base and the positive impact of related diversification in drawing upon existing core capabilities. Furthermore, strategic change proved to play a significant role in aiding the reversal in performance decline.